A soaring minaret: Abu Bakr al-Wasiti and the rise of Baghdadi sufism - Silvers, Laury (State University of New York Press, 2010)
Wasiti and early sufism -- Wasiti's intellectual heritage -- Wasiti in Iraq -- Wasiti in Khurasan -- Wasiti and Sufi discourse -- Wasiti's theology -- Theological principles -- God's essence -- The attributes -- The acts -- Conclusion